Plan estratégico para la granja de producción agropecuaria la isabela de la parroquia Timbara, cantón Zamora, provincia de Zamora Chinchipe - Calderón Sarmiento, Jorge Arturo (2015)
The present investigation STRATEGIC denominated "PLAN FOR THE FARM OF AGRICULTURAL PRODUCTION ISABELA OF THE PARISH TIMBARA, CANTON ZAMORA, COUNTY DE ZAMORA CHINCHIPE", has for objective to improve the production of the farm, for that which left then of the realization of a diagnosis that allowed to identify the weaknesses and strengths of the farm, they thought about the strategies and the respective projects. The property Isabela has a surface of 15 there is, her floors are fumíferos and loamy, the horizon is of black color with good drainage. The topography of the property in its majority is to regulate, with small areas of slopes. The climate of the sector where the property is it is warm humid with a temperature I average yearly of 25º C., with ends among 24º at 26ºC. The property has enough it dilutes, in reason that for the same one the gulch runs Tunantza that drives clean water in permanent form, and it is good for water trough of the animals. Inside the socioeconomic aspects, the property is located to 3 Km of the parish Timbara; and to 9 Km of Zamora's city. The communication among Timbara with Zamora's city is given by means of a highway of first order. The housing house has electric power and it dilutes treated. As cultivations, the property possesses 12 there are of grass elephant and gramalote; 0,5 have of banana and 0,5 there is of yucca and 1 have of constructions like a chanchera and four ponds for tilapia. Inside the cattle raising, the property has 15 heads of bovine livestock of the race Holstein, of which 4 produce milk, with a production of 12 daily liters in total; 150 pigs of race also exist Yorkshire (30 reproducers and 120 of it puts on weight). 6 Among the weaknesses of the property he/she is: The property lacks a work plan to carry out its activities. A good organization is not observed in the work of the property. It is not given pursuit and control of the work. The owner has limited knowledge it has more than enough Administration of properties. It lacks registrations of the production. The revenues and utilities of the property are low. Accounting is not taken. In the property it doesn't use technology. Absence of appropriate teams for the handling of the bovine ones and the piscicultura. Plan lack for the technical handling to the bovine ones. The production of milk is low (3 lts / it vacates / day). The reproduction of the bovine ones is for it mounts natural. It lacks a sanitary calendar for bovine. The feeding of the livestock is only with the help of grass elephant and gramalote that are of bad quality. Supplementary null feeding to the bovine ones. The bovine ones have external parasites as it obstructs and tick. To the pigs a good feeding is not given. The pigs delay a lot of time in reaching the necessary weight. Desparasitación absence to pigs. The pools for the trouts are rustic. The feeding of the fish is with having not balanced appropriate for tilapia. The tilapia production is low. The herdsmen of the property deforestados are. The workers of the property don't have technical knowledge. Regarding the strengths it is determined that: The owner of the property doesn't have debts with banks neither cooperative. Good genetics of the pigs of the property. The property has clean abundant water. Good yucca production and of banana. The Topography of the property is flat in its surface majority. The main projects and activities of the plan are the following ones: Execution of qualification events on the form of organizing farms. Organization of qualification events has more than enough control of the work of the farms. 7 Organization of qualification events has more than enough Administration of Farms. A technician's recruiting so that it designs the registrations of the production for the property. Genetic improvement of the bovine cluster of the farm. A technician's recruiting so that it takes the accounting and carry out the balances and financial states. Organization of qualification courses in the technical handling of the production of the farm. Equipment for the handling of the bovine cluster and piscícola of the farm. Design and execution of a vaccination calendar and desparasitación in the property. Renovation of grass in the farm. Formulation of a supplementary portion for the bovine ones according to their nutritional requirements. Elaboration of the desparasitación calendar for bovine. Formulation of nutritious portions for the pigs. Readecuación of the pools for existent fish. Improvement of the feeding of the fish with having balanced specific for tilapia. The herdsmen's reforestation with leguminous arboreal species to improve the floors of the prairies and to give shade. Organization of qualification courses on handling technician of agricultural farms for the owner and their children.